Is Dyslexia a Brain Disorder? - Athanassios Protopapas (Brain Sciences, 2018)
Specific word reading difficulty, commonly termed ‘developmental dyslexia’, refers to the low end of the word reading skill distribution but is frequently considered to be a neurodevelopmental disorder. This term implies that brain development is thought to be disrupted, resulting in an abnormal and dysfunctional brain. We take issue with this view, pointing out that there is no evidence of any obvious neurological abnormality in the vast majority of cases of word reading difficulty cases. The available relevant evidence from neuroimaging studies consists almost entirely of correlational and group-differences studies. However, differences in brains are certain to exist whenever differences in behavior exist, including differences in ability and performance. Therefore, findings of brain differences do not constitute evidence for abnormality; rather, they simply document the neural substrate of the behavioral differences. We suggest that dyslexia is best viewed as one of many expressions of ordinary ubiquitous individual differences in normal developmental outcomes. Thus, terms such as “dysfunctional” or “abnormal” are not justified when referring to the brains of persons with dyslexia.